ChemInform Abstract: One‐Pot versus Sequential Reactions in the Self‐Assembly of Gigantic Nanoscale Polyoxotungstates. Issue 25 (3rd June 2013) - Gao, Jing; Yan, Jun; Beeg, Sebastian; Long, De‐Liang; Cronin, Leroy
Abstract Compound (III) gives rise to a series of giant nanomolecular species.